Social media choice of generations Y and Z in the portuguese market - Carvalho, João M. S. (2022)
The growing acceptance and use of social media are influencing marketing practices and the way brands communicate with customers and look for ideas on new products, services, and offer improvements. The use of social media is crucial in today’s marketing strategy, promoting constant interaction with customers and impacting on their decision-making processes. The purpose of this study is to know what social media platforms are preferred by people from Generations Y and Z and why. By providing specific insights, this study shows differences between Y and Z individuals and outlines that all brands must carefully plan which platforms are most useful for their business, as well as decide what to communicate and share in order to create win–win situations. The results show, in addition to the study of other social media, that Facebook is the preferred platform in all motivational factors for Generation Y and Instagram for Z, which implies that marketers must act in accordance with these preferences depending on their target audiences.